Evaluation of infants with HIV-infected mothers and perinatal transmission in Turkey: A single-center experience - KEPENEKLİ KADAYİFCİ, EDA; YAKUT, NURHAYAT (KARE PUBL, 2021)
OBJECTIVE: The most common route of HIV infection in children is through perinatal transmission. In this study, we aimed to evaluate the characteristics of infants with HIV-infected mothers and perinatal HIV transmission. METHODS: We conducted a retrospective, single-center study of HIV-exposed infants in between December 2017 and October 2019 in a Marmara University Pendik Training and Research Hospital. RESULTS: A total of 18 infants were examined. All babies were born by cesarean section, and none of them were breastfed. Seventeen mothers were diagnosed with HIV before pregnancy. These mothers had received antiretroviral therapy (ART) during pregnancy, and their viral loads before delivery were negative. An antiretroviral prophylaxis with oral zidovudine was started in all infants within their 1st day of birth and continued for at least 6 weeks. All infants were tested for their HIV viral load within the first 48 h of birth, with negative results, and 12 infants were tested for anti-HIV antibodies at the 18th month, again with negative results. In this study, we determined that none of the infants had been infected with HIV. CONCLUSION: Our findings highlight the importance of initiating ART for all HIV-infected pregnant women and the importance of protection modalities during pregnancy, delivery, and the postnatal period for the prevention of perinatal transmission of HIV.
Keywords: Children; HIV; infection; perinatal transmission; Turkey; TO-CHILD TRANSMISSION; ANTIRETROVIRAL THERAPY; EXPOSED INFANTS; PREVENTION; WOMEN; RATES